Liberal principles for social welfare relations in infinitely-lived societies - Michele Lombardi; Roberto Veneziani (Queen Mary University of London, Department of Economics, 2009)
This paper extends the analysis of liberal principles in social choice recently proposed by Mariotti and Veneziani (2009a) to infinitely-lived societies. First, a novel characterisation of the inegalitarian leximax social welfare relation is provided based on the Individual Benefit Principle, which incorporates a liberal, non-interfering view of society. This result is surprising because the IBP has no obvious inegalitarian content. Second, it is shown that there exists no weakly complete social welfare relation that satisfies simultaneously the standard axioms of Finite Anonymity, Strong Pareto, and Weak Preference Continuity, and a liberal principle of Non-Interference that generalises IBP.
Keywords: D63; D70; Q01; 330; infinite utility streams; Individual Benefit Principle; leximax; non-interference; impossibility; Liberalismus; Public Choice; Soziale Lage; Theorie